Continuous process of carbon nanoparticles generation by the plasma-liquid system "tornado" type - Veremii, Iu.P.; Iukhymenko, K.V.; Kasumov, M.M.; Lisitchenko, T.E. (Вопросы атомной науки и техники, 2014)
Plasma-catalytic system for generation of carbon nanomaterials based on tornado-type discharge (using reverse-vortex gas flow) in a mixture of ethanol aerosol and inert gas was studied. Current-voltage characteristics of the discharge for different modes of the system were investigated. Efficiency of the systems with metal and graphite electrodes was compared. The possibility of continuous operation of such plasma-liquid reactor combined with pyrolytic chamber was demonstrated. It was shown that different morphology of carbon structures (nanorods and nanotubes) generated in such plasma system depends on the temperature of pyrolytic chamber and electrode materials. Представлены плазменно-каталитические системы для генерации углеродных наноматериалов на основе разряда типа "торнадо" (с использованием обратно-вихревого потока газа) в смеси аэрозоля этанола и инертного газа. Рассмотрены вольт-амперные характеристики такого разряда для различных режимов работы системы. Проведено сравнение эффективности системы с металлическими и графитовыми электродами. Показана возможность непрерывной работы такого плазменно-жидкостного реактора в сочетании с пиролитической камерой. Показана возможность образования в такой системе углеродных структур различной морфологии (наностержней и нанотрубок) в зависимости от температуры пиролитической камеры и материала электродов. Представлено плазмово-каталітичні системи для генерації вуглецевих наноматеріалів на основі розряду типу "торнадо" (з використанням обернено-вихрового потоку газу) в суміші аерозолю етанолу та інертного газу. Розглянуто вольт-амперні характеристики такого розряду для різних режимів роботи системи. Проведено порівняння ефективності системи з металевими та графітовими електродами. Показана можливість безперервної роботи такого плазмово-рідинного реактора в поєднанні з піролітичною камерою. Показана можливість утворення в такій системі вуглецевих структур різної морфології (нанострижнів і нанотрубок) в залежності від температури піролітичної камери та матеріалу електродів.